In defense of troublemakers the power of dissent in life and business - Charlan Nemeth (New York Basic Books, 2018)
Introduction: fear consensus love dissent -- Majorities versus troublemakers: the art of persuasion -- Numbers rule -- Even one dissenter makes a difference -- Dissent as an art in changing hearts and minds -- Consensus versus dissent: consensus closes the mind but dissent opens the mind -- Consensus narrows thinking and kills rationality -- Dissent diversifies and strengthens thinking -- Groupthink versus groups of thinkers: groups often make terrible decisions, but can make better ones when we encourage discussion and dissent -- Group decisions: often in error never in doubt -- Diversity and devil's advocates -- Conclusions -- Acknowledgments -- Notes -- Index.
Includes bibliographical references and index.
Keywords: Social psychology